2020
DOI: 10.2147/opth.s260998
|View full text |Cite
|
Sign up to set email alerts
|

<p>Oral Spironolactone versus Conservative Treatment for Non-Resolving Central Serous Chorioretinopathy in Real-Life Practice</p>

Abstract: Objective: To compare the efficacy of oral spironolactone treatment versus conservative treatment for patients with persistent central serous chorioretinopathy (CSC) in real-life practice. Design: Retrospective comparative study. Patients and Methods: Medical records and retinal images of 62 patients with nonresolving CSC were reviewed. Twenty-one patients received oral spironolactone (50 mg/ day) while 41 patients received conservative treatment. Primary outcome was proportion of eyes with complete resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Rifampin is a cytochrome P450 and 3A4 inducer and thus increases the processing of endogenous steroids through the induction of hepatic metabolism [34,35]. It was considered an off-label treatment after the alleviation of chronic CSC was observed in a patient who was on multi-drug antibiotic therapy for presumed latent tuberculosis, which was an effect that persisted on rifampin monotherapy [26]. Despite these positive outcomes, the exact role of corticosteroids in CSC pathogenesis is inadequately understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampin is a cytochrome P450 and 3A4 inducer and thus increases the processing of endogenous steroids through the induction of hepatic metabolism [34,35]. It was considered an off-label treatment after the alleviation of chronic CSC was observed in a patient who was on multi-drug antibiotic therapy for presumed latent tuberculosis, which was an effect that persisted on rifampin monotherapy [26]. Despite these positive outcomes, the exact role of corticosteroids in CSC pathogenesis is inadequately understood.…”
Section: Resultsmentioning
confidence: 99%
“…Given that corticosteroids are involved in CSC formation, glucocorticoid inhibition has been recommended as a possible therapeutic method [16][17][18][19][20][21][22]. Small-scale case series support the role of systemic anti-corticosteroid agents, including mifepristone, ketoconazole, finasteride, and rifampin, in the treatment of CSC [6,[23][24][25][26][27]. A few studies recently examined the impacts of mineralocorticoid receptor antagonists on CSC and endorsed the use of these agents in treating the disease [28][29][30], but these medications have not been included in the treatment protocols for CSC.…”
Section: Introductionmentioning
confidence: 99%
“…Most results have shown positive outcomes demonstrating a significant reduction of SRF, decreased central macular thickness (CMT), and improvement in VA [ 57 , 130 , 131 ]. Although oral spironolactone is not a first-line treatment, it is helpful for patients with non-resolving CSCR with SRD [ 132 ]. The VICI study found that oral eplerenone (25 mg/day for 1 week then increasing to 50 mg/day for up to 12 months) was not superior to placebo for improving VA in people with cCSCR at 12 months [ 133 ].…”
Section: Treatmentmentioning
confidence: 99%
“…It is a unilateral condition, usually affecting young and middle-aged adults, with a male predominance. 1,2 Common risk factors include type A personality, male gender, steroid use, stress, pregnancy, alcoholism, smoking, H. pylori infection and hypermetropia. 3 Patients present with blurring of vision, metamorphopsia, micropsia and mild dyschromatopsia.…”
Section: Introductionmentioning
confidence: 99%